O senso religioso na forma????o em psicologia no Brasil: uma an??lise dos curr??culos universit??rios - Piasson, Douglas Leite (2017)
The subject of this study refers to the religious sense in the university professional formation of the Brazilian psychologist. Since its regulation as a profession, Psychology has been directing efforts to train and train qualified professionals to work in the various areas of the psychological field. This concern emerges, mainly, from the 70s, due to the economic and political scenario experienced in the country. Among the contemporary demands that are present in this complex professional scenario, more and more have sought to understand those who enjoy the psychological services from the perspective of the integrality of the person, requiring the psychologist a qualification consistent with this reality. In this context, it reemerges the theme of religious sense, a theme present since the beginning of Psychology, but silenced during consecutive decades throughout much of the twentieth century, and which is increasingly gaining the current scenario of productions in the area. However, it is still a field full of challenges and lacking in advances, especially with regard to the training of professionals in this area in order to enable a more appropriate and committed action with the socio-cultural reality where it is inserted. Given the importance of religiosity for the Brazilian population, and this dimension being necessary for the training of professionals qualified to act in a competent, sensitive and ethical manner, this dissertation had the general objective to investigate "if", "how much" and "how" the theme of the religious sense has been approached in undergraduate curricula in psychology in Brazil. For this, a methodological stance of mixed research was adopted, employing documentary research techniques as the main research resource, focusing on the analysis of undergraduate curricula in psychology of Brazilian universities. It was verified that the subject has been approached in the Brazilian universities, being present in about 20% of the analyzed institutions, being mostly universities located in the Southeast region, private for-profit institutions and Catholic confessional vote. The general analysis of the disciplines points to the predominance of theoretical disciplines, assuming a compulsory character, when in institutions with confessional vote and optional character in the universities without explicit confessional vote, with a workload of 60 hours, distributed in 4 credits and offered in the first half of the psychology course. As for the disciplines that come specifically from psychology, they have an optional character and have been more frequently named Psychology of Religion, despite the identification of a rich diversity of names, more emphatically addressing conceptual and historical aspects in their contents, having as main focus of study the concept of Religious Experience. It discusses the importance of the resumption of the theme in the spaces of professional training of the psychologist, proposing the insertion of specific disciplines that deal with the subject in the undergraduate from the interlocution between theory and practice in the field.